Comparative Constructions in Guajiro/Wayuunaiki - ílvarezJosé (Opción)
<!–[if gte mso 9]> Normal 0 21 false false false ES-VE X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoPapDefault mso-style-type:export-only; text-align:justify; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 80.4pt 70.85pt 63.8pt; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> We describe comparative structures like Müliashi ma”™i Luuka nuulia Kamiirü ”˜Lucas is poorer than Camilo”™ in Guajiro/Wayuunaiki within a typological approach. Dixon (2004) proposes a prototypical comparative scheme using the notions of (in the English translation): COMPAREE Lucas, STANDARD OF COMPARISON Camilo, PROPERTY or PARAMETER (is) handsome, INDEX -er and MARK than. In the basic comparative construction of Guajiro, the PARAMETER is commonly a stative verb (and less frequently active verbs and adverbs) with the COMPAREE as subject. Although the INDEX can be zero, its presence frequently ensures a comparative reading with active verbs, where it can even have two exponents (in the verbal morphology and as an adverb). The INDEX is thus a discontinuous property with several exponents, one of which may even be suffixed to the MARK. The direct object can be the COMPAREE, while another object is the STANDARD. The subjective conjugation seems to be employed more often than the objective conjugation in comparative structures. The comparison of equality requires a biclausal construction where the PARAMETER is expressed as the verb of a clause with the COMPAREE as subject, and the verb maa heading a second clause with the STANDARD as subject. The comparison of inequality is formed by simple negation of the predicate. The expression of superlativity uses three strategies: a comparative construction with the STANDARD specified as a large/total set, a cleft construction, or the mere absence of the STANDARD but presence of INDEX (for absolute superlatives). When comparing two PARAMETERS in one PARTICIPANT, the INDEX is suffixed to the MARK. Finally, we examine correlative comparisons.